Der geeichte Eichpunt - niederländische Kultur um 1650 europäisch kontextualisiert: ’Bevochten eendracht’ von Willem Frijhoff und Marijke Spies - Schilling, H. (BMGN - Low Countries Historical Review, 2002)
The paper evaluates the 1650-IJkpunt-volume as a well-conceptualized and well-written example of up-to-date, national cultural history in a European perspective, which should serve as a historiographical model for research and syntheses on other national cultures and histories in early modern Europe. It comments in detail first on the theoretical and methodological principles of research and writing on early modern European societies after the end of the continent’s division into two power blocs (§ I). Second, on the implications of ’time’ and ’space’, in which 1650 acts as a starting point for both the geographical meaning of ’Europe’ and its cultural history, and it is argued, from a cultural perspective, that a specific type of Latin-European civilization should be distinguished from the Orthodox-European type of civilization on the one hand and from the transatlantic offshoots of Latin civilization on the other. Research should focus on the exchange between these different civilizations, with emphasis on the benefits and returns of this exchange for Latin Europe, especially for the agents of European expansion such as Dutch society (§ II). Finally, the paper focuses in more detail on issues such as the meaning of education and literature, political culture, the relationship between Church and State and tolerance within early modern Dutch society and culture. This review is part of the discussion forum IJkpunt 1650.